Forces on Jacket Structures: Effects of Directionality and Spectral Shapes - Ong, Zhen Liang (Universiti Teknologi PETRONAS, 2021)
In Malaysia, the majority of oil platforms are comprised of jacket structures. Despite reassessments having been conducted regularly, existing jacket structures might be subjected to conditions more critical than ever due to numerous reasons which include the plan of utilizing the existing structures beyond its design life. Furthermore, the existing structures are only designed to withstand regular wave loadings without considering other load cases which raises even more concerns about the structural integrity. Hence, this work aims to assess the structure under irregular wave loadings, compare the loadings on the structure under the effects of directionality and different spectral shapes. The research methodology is divided into three main stages.